Objective Prerequisites of Political and Legal Institutions - Jurkūnaitė, Gema (Problemos, 1980)
A pre-Marxist motivation of the existence of social institutions is found to be dualistic: these institutions were thought to be a result of human activity or agreement, and had to stand in accordance with the will of God or human nature. Since human nature was considered unchangeable, the basis of these institutions was found to be objective in either case in the sense that they did not depend on human will. The present paper puts forward an assumption that, from the point of view of Marxist social theory, the objective prerequisites of social institutions depend on the economic structure of society. Objective criteria for the evaluation of the functioning of social institutions are found in a regular development of the economic structure.